Discovery of DS-5272 as a promising candidate: A potent and orally active p53–MDM2 interaction inhibitor. Issue 10 (15th May 2015) - Miyazaki, Masaki; Uoto, Kouichi; Sugimoto, Yuuichi; Naito, Hiroyuki; Yoshida, Keisuke; Okayama, Tooru; Kawato, Haruko; Miyazaki, Masaya; Kitagawa, Mayumi; Seki, Takahiko; Fukutake, Setsuko; Aonuma, Masashi; et al.
Graphical abstract: Abstract: We have published p53–MDM2 interaction inhibitors possessing a novel dihydroimidazothiazole scaffold. Although our lead compound1 showed strong antitumor activity with single oral administration on a xenograft model using MV4-11 cells harboring wild-type p53, it needed a higher dose (200 mg/kg) for distinct efficacy. We executed further optimization with the aim of improvement of potency and physicochemical properties. Thus optimal compounds were furnished by introducing fluorine moieties onto the phenyl ring at the C-6 position and the pyrrolidine part at the C-2 substituent; and modifying the terminal piperazine to 4, 7-diazaspiro[2, 5]octane variants. Furthermore, replacing 4-chlorophenyl on the C-5 position with pyridyl variant decreased nonspecific cytotoxicity significantly. Our exploration afforded DS-5272 indicating excellent antitumor efficacy from a dose of 25 mg/kg on SJSA-1 xenografted models with high safety and good PK profiles, which has appropriate potency as a clinical candidate.